Klasifikasi aż-Żahabī atas Posisi Kitab ‘Arā’is al-Bayān fī Ḥaqā’iq Al-Qur’ān Karya Ruzbihan Baqlī asy-Syīrāzī - Saiful El-Mishry (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
Muḥammad Ḥusain aż-Żahabī classifies Sufi interpretations into two categories, naẓarī and isyārī. Further, aż-Żahabī makes a list of the Sufi isyārī books which includes the commentary ‘Arā’is al-Bayān fi Ḥaqā’iq al-Qur’ān by Ruzbihan Baqlī asySyīrāzī. However, if it is closely examined, the book is not accompanied by ẓāhir (outward) interpretation. Using historic-philosophical approach, this paper gets several conclusions. Firstly, the interpretation of asy-Syīrāzī has a close relation to the philosophical ideas of Sufism, so the book is not appropriate to be called isyārī. Secondly, the book cannot be called naẓarī either, because it has a close relationship with Sunnite Sufis such as that of al-Qusyairī and at-Tustarī. Thirdly, the concept of Sufistic interpretation of aż-Żahabī is ineffective because it does not accommodate the analysis of up and down of historical context of asy-Syīrāzī and its relation to the history of Sufism and Sufistic interpretation of the Qur’an. Fourthly, the position of the book Arā’is al-Bayān and asy-Syīrāzī in the historical development of Sufism is that after consolidation between philosophical sufism and Sunnite sufism, especially with the arrival of al-Ghazālī. Therefore, in addition to its interpretation which is related theoretically to philosophical Sufism, the book is also related to practical Sufism of the Sunnite. KeywordsAż-Żahabī, asy-Syīrāzī, ‘Arā’is al-Bayān, Sufistic interpretation.